Mental Health and Integration: A Qualitative Study on the Struggles of Recently Arrived Refugees in Germany - Lena Walther (Frontiers Media S.A., 2021)
Introduction: Forcibly displaced people are at particular risk of mental health problems and also face specific integration challenges upon resettlement. Existing literature suggests that there may be a bidirectional relationship between mental health and integration. The present study seeks to understand the relationship between integration processes and mental health problems or significant negative emotional experiences among adult refugees in Germany.Method: Applying a qualitative approach, we conducted 54 semi-structured interviews with refugees and asylum seekers who arrived in Germany between 2013 and 2018 currently residing in Berlin, Leipzig, or the Duisburg area in North Rhine-Westphalia. Data was collected between December 2018 and September 2019. We analyzed transcripts inductively using thematic analysis.Results: Five themes covering the various links between integration and mental health problems or significant negative emotional experiences were identified. First, we found that the mental health consequences of past adverse experiences, as well as ongoing worries about those left behind in the homeland, can seriously impede refugees' ability to pursue activities key to integration. Second, the process of applying for and securing asylum can result in uncertainty and fear, which, in turn, burden the individual and may impact motivation for integration. Third, many of our participants described mental health ramifications related to feeling stuck and thwarted in the pursuit of building a life, especially in securing employment. Fourth, some participants described feeling so overwhelmed by fundamental tasks throughout the integration process, namely, language learning and bureaucratic processes, that these take a psychological toll. Fifth, we identified several forms of social disconnection between refugees and members of the host community due to xenophobia, social and cultural differences, physical and emotional isolation in refugee camps, as well as with co-nationals and fellow refugees. Negative emotions, mistrust, and socio-cultural differences that emerge throughout the integration processes seem to erode social cohesion among refugee communities, potentially further threatening mental health.Conclusion: Mental health problems and integration processes appear to be closely related across different areas of integration. Innovative solutions to challenges identified by members of the refugee community in Germany stand to benefit mental health and integration outcomes simultaneously.